Design, Synthesis and Computational Study of Fluorinated Quinoxaline‐Oligothiophene‐based Conjugated Polymers with Broad Spectral Coverage. Issue 24 (28th November 2018) - Gedefaw, Desta; Hedström, Svante; Xia, Yuxin; Persson, Petter; Andersson, Mats R.
Abstract: Donor‐acceptor (D‐A) copolymers typically show two absorption peaks in the visible region, flanking a valley region of limited absorptivity. One strategy for more panchromatic light harvesting is to incorporate side‐groups orthogonal to the polymer backbone, which enable 2D π conjugation and can give rise to additional absorption peaks. Here we design and synthesize two D‐A polymers which both carry a fluorinated quinoxaline acceptor unit, but whileP1 includes a benzodithiophene donor moiety with thiophene side‐groups (2D‐BDT), theP2 polymer lacks 2D conjugation in its simpler pentathiophene donor segment. TheP1 polymer consequently shows an atypical absorption profile with more panchromatic absorption with no apparent valley in the spectrum. In order to understand the structure‐electronic relations, the optical and electrochemical properties were predicted using a previously developed computational approach. The predicted optical properties show very good agreement with the experimental results. Solar cells made fromP1 show a short‐circuit current more than twice as large asP2, attributed to its enhanced spectral coverage. However, poor fill factors limit the preliminary power conversion efficiencies to 3.3 % forP1 and 1.0 % forP2 as blended with PCBM[70] in a 1 : 1.5 (w/w) ratio. Abstract : Panchromatic absorption is achieved in the donor‐acceptor (D‐A) polymerP1 by incorporating conjugated side groups (SG) on the donor, enabling 2D π conjugation and giving rise to an additional absorption peak in the visible spectrum. As a result, improved short‐circuit currents are obtained in solar cells made from the polymer. Time‐dependent density functional theory is used to characterize the molecular‐orbital origin of the absorption peaks.